Western Hemisphere quality and production capacity of soybean protein - Cerrudo, Anibal; Miller-Garvin, Jill; Naeve, Seth L. (Frontiers in Sustainable Food Systems, 2023)
Soybean’s protein concentration and amino acid profile vary geographically due to genotype and environment. We used 1817 on-farm grain samples from the United States, Brazil, and the Southern Cone to assess soybean protein variability in the Western Hemisphere, which accounts for 85% of global production. Our analysis found consistent spatial patterns for protein concentration and amino acid composition, with differences in protein concentration of up to 5.4% among regions. While there was a negative correlation between protein concentration and the abundance of critical amino acids (lysine, cysteine, threonine, methionine, and tryptophane), their amount per ton of grain increased with protein concentration. Our findings can guide market and industry in benchmarking soybean protein quality across the Western Hemisphere, which according to our projection could supply close to 120 million metric tons of protein and 17 million metric tons of the most critical amino acids annually by 2030.